2019
DOI: 10.1093/eurheartj/ehz746.0902
|View full text |Cite
|
Sign up to set email alerts
|

P6305Activation of invariant natural killer T cells ameliorates doxorubicin-induced cardiomyopathy

Abstract: Background Invariant natural killer T (iNKT) cells orchestrate tissue inflammation via regulating various cytokine productions, especially strongly upregulating interferon (IFN)-γ. Activation of iNKT cells have been previously reported to exert protective effects against post-infarcted cardiac remodeling and cardiac ischemia/reperfusion injury. However, the role of iNKT cells has not been determined in doxorubicin (DOX)-induced cardiomyopathy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Among the 20 highest-cited references, six articles explored the mechanisms of doxorubicin-induced acute cardiotoxicity (Chatterjee et al, 2010;Octavia et al, 2012;Sawaya et al, 2012;Zhang et al, 2012;Tacar et al, 2013;Cardinale et al, 2015), and the important keywords of oxidative stress, apoptosis, and expression were in red cluster. Oxidative stress and apoptosis play pivotal roles in cardiotoxicity, and several signaling pathways are implicated in mediating these processes (Paradies et al, 2018;Ikeda et al, 2019;Tian et al, 2020;Timm and Tyler, 2020;Wallace et al, 2020;Ahsan et al, 2021;Borisov et al, 2021;Li et al, 2021;FIGURE 5 The visualization of co-citation reference.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%
“…Among the 20 highest-cited references, six articles explored the mechanisms of doxorubicin-induced acute cardiotoxicity (Chatterjee et al, 2010;Octavia et al, 2012;Sawaya et al, 2012;Zhang et al, 2012;Tacar et al, 2013;Cardinale et al, 2015), and the important keywords of oxidative stress, apoptosis, and expression were in red cluster. Oxidative stress and apoptosis play pivotal roles in cardiotoxicity, and several signaling pathways are implicated in mediating these processes (Paradies et al, 2018;Ikeda et al, 2019;Tian et al, 2020;Timm and Tyler, 2020;Wallace et al, 2020;Ahsan et al, 2021;Borisov et al, 2021;Li et al, 2021;FIGURE 5 The visualization of co-citation reference.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%
“…In a study reported in this issue of JACC: Basic to Translational Science , Sada et al 3 investigated the hypothesis that activation of iNKT cells by α-GC attenuates Dox-induced cardiomyocyte death and explored the underlying molecular mechanisms. To do this, the investigators used α-GC to activate iNKT cells, confirmed its cardioprotective role in Dox cardiotoxicity, and defined the downstream role of IFN-γ–signal transducers and activators of transcription 1 (STAT1)– extracellular signal-regulated kinase (ERK) pathway.…”
mentioning
confidence: 99%
“…To do this, the investigators used α-GC to activate iNKT cells, confirmed its cardioprotective role in Dox cardiotoxicity, and defined the downstream role of IFN-γ–signal transducers and activators of transcription 1 (STAT1)– extracellular signal-regulated kinase (ERK) pathway. After validating α-GC as an activator of iNKT in Dox-treated hearts, Sada et al 3 found that α-GC prevents Dox-induced weight loss and cardiac dysfunction. Using echocardiography, the investigators found that administration of α-GC attenuated Dox-induced cardiac dysfunction, as well as attenuated cardiac atrophy.…”
mentioning
confidence: 99%
See 2 more Smart Citations